Feasibility of markerless tumor tracking by sequential dual-energy fluoroscopy on a clinical tumor tracking system. Issue 3 (December 2015) - Dhont, Jennifer; Verellen, Dirk; Poels, Kenneth; Tournel, Koen; Burghelea, Manuela; Gevaert, Thierry; Collen, Christine; Engels, Benedikt; Van Den Begin, Robbe; Buls, Nico; Van Gompel, Gert; Van Cauteren, Toon; et al.
Abstract: A novel approach to dual-energy imaging for markerless tumor tracking was proposed consisting of sequential dual-energy fluoroscopy, omitting the need for fast-switching kV generators. The implementation of this approach on a clinical tumor tracking system and its efficacy is shown feasible through optimization of the imaging parameters.